Acute Water Supplementation Improved the Body Composition of Young Female Adults After Water Restriction of 12 h in Baoding, China: A Randomized Controlled Trial (RCT) - Zhang, Jianfen; Zhang, Na; Du, Songming; Liu, Shufang; Ma, Guansheng (Frontiers in Nutrition, 2022)
The insufficient intake of water may influence the balance of water in the human body. The purposes of the current study were to explore the impacts of water supplementation on body composition among young adults with 12h water restriction and to investigate the optimum volume of water for improving body composition. A randomized controlled trial study was conducted among 64 young males and females in Baoding, China. Being fasted overnight for 12 h, at 8:00 a.m. of day 2, anthropometric measurements and the samples of urine and blood were collected as baseline test. Body composition was determined by measuring the ECW (extracellular water), ICW (intracellular water), and TBW (total body water) using bioelectrical impedance analysis (BIA). The participants were randomly divided into four groups, including water supplementation (WS) group 1, 2, and 3 with 500, 200, and 100 mL of water and a no water supple-mentation group (NW group). After 90 min, they were reassessed as rehydration test (at 10:00 a.m. of day 2). Repeated measurements ANOVA was used to assess the impact of water supplementation on body composition. Comparing the baseline and rehydration tests, interactions between time and volume were not significant among the males (all p>0.05). Among females, a significant interaction was only found in ECW (p=0.043), with TBW tending towards being significant (p=0.055); comparing the baseline with rehydra-tion tests, the ECW in WS group 1, WS group 3, and NW group all decreased (p=0.028, p=0.001, and p=0.029), with reductions of 0.1, 0.3, and 0.2 kg, respectively; no significant decrease was found in WS group 2 (p=0.329). Furthermore, comparing the WS groups with NW group in rehydration test, the differ-ences did not differ significantly (p=1.000; p=1.000; p=0.288), respectively. Between males and females within group, all the indexes of body composition differed significantly, both at baseline and rehydration tests (all p<0.05). Water supplementation could lead to changes in the distribution of the water content of body composition of young female adults in the present study, but not males, after 12 h of water restriction, with no decrease in ECW.